2004
DOI: 10.1080/08039480410006232
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of traumatized refugee children with eye movement desensitization and reprocessing in a psychodynamic context

Abstract: This study examines the effects of a psychodynamic approach of Eye Movement Desensitization and Reprocessing (EMDR) in treatment of traumatized refugee children. Among a child psychiatric outpatient refugee team, 13 children with post-traumatic stress disorder (PTSD), were treated by EMDR incorporated in a traditional psychodynamic therapeutic approach. The Posttraumatic Stress Symptom Scale for Children (PTSS-C) and the Global Assessment of Functioning (GAF) were administered before and after the treatment, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 1 publication
0
55
0
1
Order By: Relevance
“…Three studies concerning single-incident pediatric PTSD were found to relate to EMDR [Chemtob et al, 2002b;Oras et al, 2004;Puffer et al, 1998] and some case reports [Cocco and Sharpe, 1993;Greenwald, 1998]. As in adult studies [Foa, 2000], the methodology of the CBT studies in children is superior to that of the EMDR studies.…”
Section: Eye Movement Desensitization and Reprocessingmentioning
confidence: 96%
“…Three studies concerning single-incident pediatric PTSD were found to relate to EMDR [Chemtob et al, 2002b;Oras et al, 2004;Puffer et al, 1998] and some case reports [Cocco and Sharpe, 1993;Greenwald, 1998]. As in adult studies [Foa, 2000], the methodology of the CBT studies in children is superior to that of the EMDR studies.…”
Section: Eye Movement Desensitization and Reprocessingmentioning
confidence: 96%
“…Thirteen out of 23 studies examined the effect of evidence-based treatments, such as interpersonal therapy (IPT) (Betancourt et al, 2012a), strict cognitive behavioural therapy (CBT) (Catani et al, 2009; Onyut et al, 2005; Pfeiffer & Goldbeck, 2017; Schauer, 2008; Schottelkorb et al, 2012), eclectic CBT with other elements (Ehntholt, Smith, & Yule, 2005; Möhlen, Parzer, Resch, & Brunner, 2005; Ooi, 2012; Ooi et al, 2016; Šehović, 2002; Tol et al, 2012), or eye movement desensitization and reprocessing (EMDR; within a psychodynamic therapy) (Oras, De Ezpeleta, & Ahmad, 2004). …”
Section: Resultsmentioning
confidence: 99%
“…Eight of the significant effects were achieved using CBT techniques, two in a meditation-relaxation condition (Catani et al, 2009; Schauer, 2008), one with a general education programme (Gupta & Zimmer, 2008), one with EMDR combined with psychodynamic therapy (Oras et al, 2004), one with a writing intervention (Lange-Nielsen et al, 2012), and a multilevel treatment particularly oriented to the needs of young refugees (Ellis et al, 2013). Seven of 19 calculated effect sizes for depression were significant, six of them showed positive effects between medium (SMC = 0.31, Tol et al, 2012, in the group of girls) and large (SMC = 1.98, Betancourt et al, 2012a, in the group of girls treated with IPT), with the clinically relevant results being achieved in three CBT conditions, two conditions that used IPT (Betancourt et al, 2012a), one using EMDR (Oras et al, 2004), and one using creative play (Betancourt et al, 2012a). Writing for recovery had negative effects on depression symptoms (SMC = −1.12, Lange-Nielsen et al, 2012), but beneficial effects on traumatic grief symptoms (SMC = 0.96, 95% CI [0.51, 1.41]) (Kalantari et al, 2012) (not reported in Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…As is the case with adults, studies focusing on children within migration, have primarily focused on trauma and health issues (Sack et al 1996;Thabet & Vostanis 1999;Papageorgiou et al 2000;Felsman et al 1990;ServanSchreiber et al 1998;Almqvist & Brandell-Forsberg 1997;Almqvist & Broberg 1999;Fazel et al 2012;Oras et al 2004;Goldin et al 2008). A common denominator in these studies is that they measure the impacts of being exposed to war and violence in various parts of the world, and the effects upon the mental health of children.…”
Section: Children Within Migration Researchmentioning
confidence: 99%